MODEL CAPITAL ASSET PRICING (CAPM) DAN ARBITRAGE PRICING THEORY (APT) DALAM INVESTASI SAHAM - Mustoffa, Ardyan Firdausi; Ulfah, Ika Farida; Wijianto, Wijianto (Jurnal Akuntansi dan Pajak, 2024)
The Capital Assets Pricing Model (CAPM) and Arbitrage Pricing Theory (APT) are alternatives used by investors to predict stock investment returns. However, until now it is still a matter of debate about the level of accuracy of the two. This research aims to analyze the comparison of CAPM and APT accuracy levels for predicting sharia stock returns during the Covid-19 pandemic. Secondary data in this research was obtained from the websites www.idx.co.id, www.bi.go.id. Based on CAPM, the level of return and risk have a positive and linear relationship. The risk measure which is an indicator that influences shares in the CAPM is shown by the variable Î² (beta). The greater the Î² of a stock, the greater the risk contained in it. The population in this study is stock price data for pharmaceutical sector companies listed on the IDX and consistently listed in the Jakarta Islamic Index (JII) for the 2020-2022 period. Based on research results, the CAPM is more accurate and more precise than APT. The level of accuracy of the CAPM and APT models does not indicate a significant dissimilarity in results in predicting sharia stock returns on the JII seen from the CAPM MAD value which is smaller than the APT MAD value